Music and words : producing popular songs in modern Japan, 1887-1952 - Patterson, Patrick M. (New studies in modern Japan., 2018)
This book analyzes composer Nakayama Shimpei's popular songs in the context of Japan's developing record industry and popular music market between 1887 and 1952.